Answer:
25
Step-by-step explanation:
(14÷2)×5+6(3×(4+1))÷5
using BODMAS
7×5+6(3×5)÷5
=7×5+6×15÷5
=35+90÷5
=125÷5
=25
Go one box left from the 0 an 3 down
Answer:
- 3y² - 7y + 6
Step-by-step explanation:
Given
(- 3y + 2)(y + 3)
Each term in the second factor is multiplied by each term in the first factor, that is
- 3y (y + 3) + 2(y + 3) ← distribute both parenthesis
= - 3y² - 9y + 2y + 6 ← collect like terms
= - 3y² - 7y + 6
Answer:
b)11
since 11^2 is 11*11 = 12
and when you take the square root of 121
we get 11
(in b- √11^2) , it cancels out the square
square root cancels square since they perform opposite functions
Answer:
I think A
Step-by-step explanation:
srry if wrong
i hope this helps tho